THU0281 SALIVARY GLAND ULTRASOUND FINDINGS ARE ASSOCIATED WITH CLINICAL AND SEROLOGIC FEATURES IN PRIMARY SJÖGREN'S SYNDROME PATIENTS. (June 2019) - Silva, Joana; Faria, Daniela; Neves, Joana; Cerqueira, Marcos; Rodrigues, Joana; Azevedo, Soraia; Alcino, Sérgio; Tavares-Costa, José; Afonso, Carmo; Peixoto, Daniela; Teixeira, Filipa
Abstract : Background: Primary Sjögren's syndrome (pSS) is a multisystem immune-mediated disease characterized by hypofunction of salivary and lacrimal glands and possible multi-organ systemic manifestations. Over the past years, three sets of diagnostic criteria have been proposed, but none included salivary gland ultrasound (SGUS). However, SGUS has been recently applied for diagnosis and there are some reports regarding the correlation of SGUS findings with immunological and serological features in pSS patients (1, 2). Objectives: To investigate the association of SGUS fndings with clinical and analytical features of pSS patients. Methods: A total of 54 patients diagnosed with pSS, fulfilling both the 2016 ACR/EULAR and 2002 AECG criteria for the disease, followed-up at our Rheumatology department, underwent SGUS evaluation. The parenchymal homogeneity of bilateral parotid and submandibular glands was graded using a score of 0 (normal) to 4 (gross inhomogeneity). Patients were classified into two groups according to the highest US score obtained. The grades 1 and 2 were considered to be normal and grades 3 and 4 to represent pathological SGUS findings. Demographics (age, sex and disease duration), European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (ESSDAI) and laboratorial data (erythrocyte sedimentation rate, autoantibodies, rheumatoid factor, hypergammaglobulinemia, β2-microglobulin and complement levels) were collected and compared between the two SGUS groups. The association between SGUS and these data was explored by multivariable analysis. Statistical significance was defined as p <0.05. Results: The mean age of patients was 57.5±13.3 years and median disease duration was 5.0 [IQR (2.75-11.25)]. The majority of the study population were women (96%) and 35% (19/54) had pathological SGUS findings. Differences between the group with pathological SGUS versus the group with normal SGUS are depicted in table 1 . Multivariate logistic regression revealed that anti-SSB ([OR] = 6.6, 95% [CI] 1.7 to 25.8, p = 0.006) was independently associated with the presence of pathological features in SGUS. Conclusion: In our study, pathological US findings were associated with higher disease activity and positivity for rheumatoid factor and anti-SSB. Additionally, anti-SSB antibody was strongly and independently associated with pathological US findings in the salivary gland of pSS patients. Further and larger studies are necessary to support these findings and include SGUS as part of the diagnostic criteria for Sjögren's syndrome. References: [1] J-W Kim, et al. Salivary gland ultrasonography findings are associated with clinical, histological, and serologic features of Sjögren's syndrome. Scand J Rheumatol 2018;00:1–8. [2] J. Nieto-González et al. Salivary gland ultrasound is linked to the autoimmunity profile in patients with primary Sjögren's syndrome. Journal of International Medical Research 2018; 0(0) 1–11. Disclosure of Interests: None declared